Pengaruh Pengungkapan Sustainability Report terhadap Kinerja Keuangan dan Implikasinya terhadap Nilai Perusahaan - Gilang Hafitri, Rifa; Novianty, Ira; Gunawan, Arwan; Afriady, Arif (Indonesian Accounting Literacy Journal, 2025)
As awareness of sustainability issues grows, there is an increasing demand from governments, investors, and communities for companies to contribute to sustainability. Transparency regarding a company's sustainability performance, as reflected in sustainability reports, is seen as a way to enhance stakeholder confidence and potentially improve financial performance and firm value. The study focuses on companies listed on the SRI-KEHATI stock index between 2017 and 2021. A purposive sampling technique is employed to select the research sample. The researchers analyze secondary data from sustainability reports available on the company's website and financial reports from the Indonesia Stock Exchange. Using path analysis with SPSS 26, the researchers draw several key findings. Firstly, the disclosure of sustainability reports positively influences firm value. Secondly, sustainability report disclosure does not directly affect financial performance. Thirdly, financial performance has a positive impact on firm value. Lastly, financial performance does not mediate the relationship between sustainability report disclosure and firm value.